School Scoliosis Screening: The Influence of Dominant Limbs and Gender - Eleni Theodorou; Marios Hadjicharalambous; Marios Tryfonidis (MDPI AG, 2024)
This study aimed to examine whether (a) there is an association of the dominant hand (DH) and leg (DL) with the side of the primary angle of trunk rotation (ATR A) and (b) there are any differences between boys and girls in the degree of the angle of trunk rotation (ATR) and the dominant hand and leg. One thousand sixty-five (age: 14 ± 3 years; height: 162 ± 13 cm; weight: 56 ± 18.7 kg; BMI: 21.18 ± 5.07) secondary school children participated in this study. Of the participants, 52.5% (n = 559) were male students (age: 14 ± 2 years; height: 166 ± 16 cm; weight: 58.7 ± 22.6 kg; BMI: 21.41 ± 5.61), and 47.5% (n = 506) were female students (age: 14 ± 3 years; height: 159.5 ± 8.5 cm; weight: 53.9 ± 14.8 kg; BMI: 21.03 ± 4.38). The ATR was measured with a scoliometer. Boys were taller and heavier (p = 0.001) and had more left DLs (p = 0.039) than girls. Girls were biologically more mature (p = 0.002), also having higher measurements for the ATR A (p = 0.004) and secondary angle of trunk rotation (ATR B) (p = 0.023) degrees compared to boys. In the general sample, only in boys, there was a significant association between the DH (p = 0.012) and DL (p = 0.001) with the ATR A side. Also, within the scoliotic group, only in boys, there was a significant association between the DH (p = 0.048) and DL (p = 0.024) with the ATR A. In conclusion, girls had higher measurements for the ATR than boys, but cross laterality was found only in boys. The results suggest different progression patterns of ATR between genders during their growth. Future research should focus on examining other possible progression mechanisms.